x^2+4y^2-4xy-4/2x^2-4xy+4x

x^2+4y^2-4xy-4/2x^2-4xy+4x

2 bình luận về “x^2+4y^2-4xy-4/2x^2-4xy+4x”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    (x^2+4y^2-4xy-4)/(2x^2-4xy+4x)
    =((x^2-4xy+4y^2)-2^2)/(2x(x-y+2))
    =((x-2y)^2-2^2)/(2x(x-y+2))
    =((x-2y+2)(x-2y-2))/(2x(x-y+2))
    =(x-2y-2)/(2x)
    @$#Edo$

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    (x^2+4y^2-4xy-4)/(2x^2-4xy+4x)
    =((x-2y)^2-2^2)/(2x(x-2y+2))
    =((x-2y-2)(x-2y+2))/(2x(x-2y+2))
    =(x-2y-2)/(2x)

    Trả lời

Viết một bình luận

Câu hỏi mới